جماليات الرمز في قصيدة جميلة بوحيرد لنزار قباني - زنينة, قبي, كوثر أميرة (University of El-oued, 2021)
نتناول في بحثنا مجموع الشعر الذي قيل في جميلة بوحيرد إبان فترة الخمسينيات و الستينيات على اعتبار جميلة رمزا أسال حبرا كثيرا وتنبع قيمة البحث من محاولتنا جمع لتحليل و تتبع كيفية تموقع الرمز فيها، ومن ثمة كان موضوع البحث يتوزع على حقول دلالية ثلاثة جميلة و الرمز و الشعر المعاصر وقد حاولنا في بحثنا، الإجابة عن أسئلة إشكالية عديدة أهمها لماذا يعتبر الشعر الشعر الحديث منصة للرمز و ماهيته و ما الجانب الأدبي و النفسي له، و ماهي أنواعه، و ما دلالة الرموز التي وظفها الشاعر وهل جميلة رمز مستهلك ومعلوك وكيف كان مستوى الإحساس الفني بالتجربة لدى نزار قباني؟. هذه بعض الأسئلة التي كانت مدار استقصائنا، وكانت بعض النتائج الهامة أجوبة لها، من أهمها أن الشعر الرمزي شعر عاصر فترة حرجة من فترات تاريخنا العربي فهو فهو بالتالي شاهد عدل على بطولاتنا، وتوحدنا و أن جميلة بوحيرد رمز ثوري تاريخي شغل حيزا هاما من الإبداع العربي على تفاوت منطقي بين الشعراء في مدى الإحساس الفني بالتجربة فقد ألفينا قصيدة نزار قباني يبدو فيها إحساس الشاعر المعذّب وحزنه، بل ووعيه بما يجري في عالمه العربي وسعيه إلى التغيير بالمشاركة الفاعلة في صنع التاريخ و كتابته شعرا إن قيمة الإحساس بالتجربة تنبع من أثره على القصيدة لغة وإيقاعا، شكلا و مضمونا و لهذا تفاوتت القدرة التركيبية للصور الشعرية له، وتمايز التلوين الإيقاعي ومن ثمة يمكن الجزم بأن الشعر الثائر لنزار المقول في جميلة شعر يستحق الالتفات إليه وهو شعر لم يقتل رحابة الرمز جميلة. In our research, we deal with all the poetry that was said in Djamila Bouhired during 1950s and 1960s, considering Djamila a symbol that was talked a lot about. The value of the research rises from our attempt to collect, analyse, and trace how the symbol is located in her. As a result , the topic of the research was distributed on three semantic fields: Djamila, symbol, and modern poem. We have tried in our research to answer many problematic questions, the most important: Why the modern poem is considered as a platform of symbol? What is its entity? What is its literary and psychological aspect? What are their kinds? What is the significance of symbols that the poet used? Is Djamila a consumed symbol? How was the level of artistic sense of the experience by Nizar Kabbani? These are some questions that were the subject of our survey. Some important results were their answers. The most important of which is that the symbolic poetry lived simultaneously with a critical period of our Arabic history. So it is a fair witness of our heroisms, and our unity. And that Djamila Bouhired a historical, revolutionary symbol that filled an important part of Arabic creativity, on a logical disparity between poets in the extent of artistic sense of the experience. We have found Nizar Kabbani's poem, that showed the poet's tormentor sense and sadness, and even his awarness of what is happening in his Arabic World, and his striving to change with effective participation in making history and writing it as a poetry. The value of the sense of the experience rise from its influence on the poem linguistically, rhymly, formly, and meanningly. As a result, his synthetic capacity of metaphor has varied. The rhythmic coloring was differentiated, from there it can be asserted that Nizar's rebellious poetry said in Djamila, is a poetry deserves attention, and it is a poetry that did not kill spaciousness of the symbol, Djamila.
Keywords: الرمز، جماليات الرمز، الشعر المعاصر; symbol, aesthetics of symbol, contemporary poetry